2014
DOI: 10.1039/c3ay41593g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of hierarchical MCM-41 spheres with an ultrahigh surface area and their application for removal of methylene blue from aqueous solutions

Abstract: Hierarchical mesoporous silica spheres were prepared by a simple sol–gel method and used for the removal of methylene blue from aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Also, the dye solubility usually increases as temperature raises weakening the adsorbate‐adsorbent interactions and impeding the adsorption process. Other authors for mesoporous silicas have previously reported this behavior …”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Also, the dye solubility usually increases as temperature raises weakening the adsorbate‐adsorbent interactions and impeding the adsorption process. Other authors for mesoporous silicas have previously reported this behavior …”
Section: Resultssupporting
confidence: 69%
“…They reported a maximum adsorption capacity for both silicas between 3.2 and 3.7 × 10 −5 mol g −1 . In addition, Qu et al reported a value of 2.4 × 10 −4 mol g −1 for the same dye using MCM‐41 obtained from sodium metasilicate. In the present work, the TBO adsorption capacity found for MCM‐41 and MCM‐48 was calculated at approximately 7.3 × 10 −5 mol g −1 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, the adsorption capacity is obviously increased by the electrostatic attraction between the negatively charged adsorbent and positively charged MB. [40][41][42][43] Three well-known adsorption models pseudo-rst-order, pseudo-second-order, Elovich were used to investigate the dynamics of the adsorption process. The adsorption model equations are listed as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Emphasis has already been placed on the fact that mesoporous materials have superior structure properties, such as large specific surface area, uniformity large pore diameter and thick silica wall, and potential apply in the fields of catalysis, adsorption, separation, drugs delivery and optical devices [1][2][3][4]. However, one main reason that these mesoporous materials have not been widely applicated in industry is their relatively poor hydrothermal stability.…”
Section: Introductionmentioning
confidence: 99%